Predictors of Age at Juice Introduction and Associations with Subsequent Beverage Intake in Early and Middle Childhood. Issue 11 (6th September 2021) - Robinson, Sonia L; Sundaram, Rajeshwari; Putnick, Diane L; Gleason, Jessica L; Ghassabian, Akhgar; Lin, Tzu-Chun; Bell, Erin M; Yeung, Edwina H
ABSTRACT: Background: The American Academy of Pediatrics recommends that if parents choose to introduce juice, they wait until ≥12 months, citing concerns of obesity and dental caries. Objectives: We sought to identify correlates of early juice introduction (<6 months) and determine whether early introduction establishes a pattern of sugary beverage intake in childhood. Methods: Upstate KIDS is a prospective birth cohort study with follow-up through 7 years ( n = 4989). The age of juice introduction was assessed from responses on periodic questionnaires from 4–18 months and categorized as <6, 6 to <12, and ≥12 months. Sociodemographic information was reported using vital records or maternal questionnaires. At 24, 30, and 36 months and 7 years, mothers reported their child's regular juice, soda, water, and milk intakes. The analysis was restricted to singletons and 1 randomly selected twin from each pair with information on juice introduction ( n = 4067). We assessed associations of sociodemographic correlates with juice introduction using Cox proportional hazard models. The relations of juice introduction with beverage intake were evaluated using Poisson or logistic regression for adjusted risk ratios (aRR) or ORs, adjusting for sociodemographic covariates and total beverage intake. Results: Of the mothers, 25% and 74% introduced juice prior to 6 and 12 months, respectively. Younger maternal age; black or Hispanic race/ethnicity; lower educational attainment; Special Supplemental Nutrition Program for Women, Infants, and Children participation (yes); smoking during pregnancy; a higher pre-pregnancy BMI; a lower household income; and living in a townhouse/condominium or mobile home were associated with earlier juice introduction. Earlier juice introduction was related to a higher childhood juice intake, any soda intake, and lower water intake, holding total beverage intake constant [aRR, 1.5 (95% CI: 1.3–1.7; P- trend < 0.0001); adjusted OR 1.6 (95% CI: 1.0–2.4; P- trend = 0.01); aRR 0.9 (95% CI: 0.8–0.9; P- trend < 0.0001), respectively]. Conclusions: Markers of lower socioeconomic status are strongly associated with earlier juice introduction, which, in turn, relates to sugary beverage intake in childhood, potentially replacing water.